Menghidupi Kesejatian Agama: Tawaran yang Menggugat Eksistensi Agama Sebagai Usaha Partisipatif dalam Pembangunan Indonesia - Edy Syahputra Sihombing (Societas Dei: Jurnal Agama dan Masyarakat, 2016)
ABSTRACK: Since human culture exist, religion is also exist in its variety. Religion has became the mode existence of human being. Basically the religion is the place to which gives space for humans to communicated, meet with the ultimate reality. In the development of human culture, religion is experiencing by a growing change in form and contents. Earlier, religion is a relationship between human and the ultimate reality, that overtime turned into an institutions that has systematically conceptualised doctrine in the form of dogmatic. The purpose of religion also shifted from efforts to more close eith the ultimate reality became human attempt to increase followers. Religion seem more concerned with quantity than quality. The shifts is likely to lead a conflict and violence to many people. This became a responsibility for Indonesians religions. This paper want to explain the truth of religion supposed and looking the positive influence of Indonesians religions in an influence of Indonesians religions in an attempt to build Indonesian become to nation that able to thrive religioan pluralism. KEYWORD: Religion, Paradigm, Ideology, Religious violence, Religious repentance, Indonesian development